PHOTOMETRIC AND SPECTROPHOTOMETRIC OBSERVATIONS OF THE CLASSICAL SYMBIOTIC STAR YY Her - Tatarnikova, A. A.; Kolotilov, E. A.; Munari, U.; Yudin, B. F. (Одеські астрономічні публікації, 2017)
The spectrophotometric and photometric observations of the classical symbiotic star YY Her both during its quiescent state and during a strong outburst in 1993 are presented.